SIMPLE AND ACCURATE METHODS OF SYOMKAS PERFORMED IN THE FORMATION OF THE EARTH (ResearchJet Journal of Analysis and Inventions, 2023)
This article provides information on simple and precise methods of S'yomkas performed in land formation, theodalite, tacheometric, menzula, phototeodalite and other methods.